New Hybrid Structure Based on Improved Switched Inductor Z-Source and Parallel Inverters for Renewable Energy Systems - Ali Zakerian; Daryoosh Nazarpour (Institute of Advanced Engineering and Science, 2015)
Nowadays, more and more distributed generations and renewable energy sources, such as wind, solar and tidal power, are connected to the public grid by the means of power inverters. They often form microgrids before being connected to the public grid. Due to the availability of high current power electronic devices, it is inevitable to use several inverters in parallel for high-power and/or low-cost applications. So, inverters should be connected in parallel to provide system redundancy and high reliability, which are important for critical customers. In this paper, the modeling, designing and stability analysis of parallel-connected three-phase inverters are derived for application in renewable energy systems. To enlarge voltage adjustability, the proposed inverter employs an improved switched inductor Z-source impedance network to couple the main circuit and the power source. Compared with the classical Z-source inverter (ZSI) and switched inductor Z-source inverter (SL-ZSI), the proposed inverter significantly increases the voltage boost inversion ability and also can increase the power capacity and the reliability of inverter systems. The proposed topology and its performances are validated using simulation results which are obtained in Matlab/Simulink.